Self Adjustment of Single Parent Mother In South Sulawesi - Indonesia - Yana Sundayani; Herry Koswara; Qadriansyah Qadriansyah (Politeknik Kesejahteraan Sosial Bandung, 2017)
This research discussed about self-adjustment of single parent mother who lives in South Sulawesi Indonesia. The aim of the research was to obtain a description about self-adjustment of single parent mother in Indonesia, including: respondent characteristic, respondent’s intellectual maturity, respondent’s emotional, respondent’s social maturity and respondent’s responsibility. The research method used quantitaive method with descriptive approach. Data collection technique used questionnaire. The measurement toll used rating scale to show the mean score of all question from range one through four. The validity test of measurement toll conducted through face validity and realibity test used Alpha Cronbach. The result was analysed through quantitaive analysis. The result showed that single parent mother has low self adjustment viewed from three of four aspects which was measured about self adjustment namely; intellectual maturity and responsibility belong to the low category. While the emotional maturity aspect is in the high category. The results of needs analysis show the mother as a single parent requires knowledge and insight as a single parent, time management ability and socialization ability. Based on the need, a program called